Erratum: Effects of trapped electrons and impurity ions on ITG modes in reversed-field pinch plasmas. (20th November 2019) - Li, J. C.; Liu, S. F.; Kong, W.; Guo, S. C.; Dong, J. Q.
Abstract: Original article: EPL, 127 (2019) 45002 .